2022
DOI: 10.3389/fmed.2022.855141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Patients With Rheumatoid Arthritis: An Updated Systematic Review and Meta-Analysis

Abstract: IntroductionRheumatoid arthritis (RA) due to systemic inflammation and insulin resistance increases the risk of cardiovascular disease and reduces life expectancy. In order to develop cardiac death prevention strategies, it is necessary to estimate the prevalence of metabolic syndrome (MetS) in these patients.MethodsThis systematic review and meta-analysis was performed to estimate the prevalence of MetS among patients with RA. International databases (i.e., Scopus, PubMed, Web of Science, and Google Scholar) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
(23 reference statements)
2
8
0
Order By: Relevance
“…We also found that MetS prevalence was significantly higher in patients aged ≥40 years than in younger patients. This finding is consistent with previous relevant studies in the general population worldwide ( 45 48 ) and in patients with SLE and RA ( 49 , 50 ) indicating that MetS is more prevalent with advancing age. No significant difference was found in MetS prevalence between male and female patients with APS regardless of the diagnostic criteria used.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that MetS prevalence was significantly higher in patients aged ≥40 years than in younger patients. This finding is consistent with previous relevant studies in the general population worldwide ( 45 48 ) and in patients with SLE and RA ( 49 , 50 ) indicating that MetS is more prevalent with advancing age. No significant difference was found in MetS prevalence between male and female patients with APS regardless of the diagnostic criteria used.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that patients with RA had an elevated prevalence of MetS,14 30 which was also common in NAFLD 10. Besides, RA and NAFLD shared similar pathogenic cytokines, such as tumour necrosis factor (TNF)-α 13 31–33.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an inflammatory autoimmune disease characterised by chronic synovitis and bone destruction and is often associated with poor life quality 13. Several epidemiological studies found a high prevalence of NAFLD-related risk factors (eg, MetS, dyslipidaemia and DM) in patients with RA 10 14–16. Besides, the therapy with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) may be another risk factor for NAFLD in RA.…”
Section: Introductionmentioning
confidence: 99%
“…1 MetS is frequently observed in patients with rheumatoid arthritis (RA). 2,3 In this regard, MetS abnormalities increase the risk of CV disease in these patients. 4,5 Prevalence of MetS among patients with RA was also associated with the activity of the disease.…”
Section: Editorialmentioning
confidence: 99%